The Influence of Social Emotional Implementation on Physical Education Learning Outcomes: Digital Technology-Based Learning Model - Saqinah, Putri Nurul; Ihsan, Andi; Arimbi, Arimbi; Ramli, Ramli; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study looks to find out how using social-emotional tools affects learning in physical education, sports, and health for students at elementary school, using a digital technology-based learning model. This study uses a quantitative approach with an experimental method. The research design used is a pre-experimental design with a one-group pretest-posttest design model. The research sample was 23 fifth-grade students at Public Elementary School Bawakaraeng I, selected using a purposive sampling technique. The research instruments consisted of a physical education outcome test, an observation sheet for the application of social-emotional learning, and a student response questionnaire. The data analysis technique used descriptive and inferential statistics in the form of a paired sample t-test with a significance level of 5%, which was preceded by an analysis prerequisite test. The results indicated that there was a significant effect of the application of social-emotional learning on physical education learning outcomes using a digital technology-based learning model. Our finding is evidenced by the t-observation value of 14.945, which is greater than the t-table value of 1.717 (14.945 > 1.717) with a significance value of 0.000 (p < 0.05). Comparison of the average pretest and posttest values showed an increase from 86.39 to 92.96, with a difference of 6.565 points. The application of social-emotional learning with a digital technology-based learning model has proven effective in improving students' physical education learning outcomes.